Predicting the Desire for Remarriage based on Self-Differentiation and Ego Strength Mediated by Irrational Beliefs in Divorced Youth - Abaie, Seyedeh Mohadese; Bagheri, Nasrin (Journal of Assessment and Research in Applied Counseling (JARAC), 2024)
Objective: The purpose of this study was to predict the desire for remarriage based on self-differentiation and ego strength mediated by irrational beliefs in divorced youth. Methods and Materials: The research method was applied in terms of purpose, descriptive in nature, and correlational in type. The population included all divorced youth in District 6 of Tehran during the years 2022-2023. In this study, 400 individuals were selected through convenience sampling using the Kramers method (2006). For data collection, the Desire for Marriage Questionnaire: Pouretemad et al. (2004), the Differentiation of Self Inventory by Skowron and Friedlander (1998), the Ego Strength Scale (ESS), and the Irrational Beliefs Questionnaire by Jones (1986) were used. Data analysis utilized descriptive statistics (mean, standard deviation) and inferential statistics (Pearson correlation and regression analysis). Findings: The results indicated that based on self-differentiation, one can predict the desire for remarriage in divorced youth (p < .01). Similarly, based on ego strength, one can predict the desire for remarriage in divorced youth (p < .01). Additionally, based on irrational beliefs, one can predict the desire for remarriage in divorced youth (p < .01). Conclusion: Therefore, it can be stated that excessive immutability and helplessness in the face of life’s challenges among divorced youth can turn into a set of irrational beliefs, consequently reducing their inclination towards remarriage. Such that irrational beliefs about helplessness against change lead to a fear of marriage, preventing the individual from accepting the responsibility of such a commitment, thus impacting the desire for marriage in the long run.